Prostaglandins and Their Receptors in Eosinophil Function and As Therapeutic Targets - Peinhaupt, Miriam; Sturm, Eva M.; Heinemann, Akos (Frontiers in Medicine, 2017)
Of the known prostanoid receptors, human eosinophils express the prostaglandin D2 (PGD2) receptors DP1 (also DP, D-type prostanoid) and DP2 (also CRTH2, chemoattractant receptor homologous molecule expressed on Th2 cells), the prostaglandin E2 receptors EP2 and EP4, and the prostacyclin (PGI2) receptor IP. Prostanoids can bind to either one or multiple receptors, characteristically have a short half-life in vivo and are quickly degraded into metabolites with altered affinity and specificity for a given receptor subtype. Prostanoid receptors signal mainly through G proteins and naturally activate signal transduction pathways according to the G protein subtype that they preferentially interact with. This can lead to the activation of sometimes opposing signaling pathways. In addition, prostanoid signaling is often cell-type specific and also the combination of expressed receptors can influence the outcome of the prostanoid impulse. Accordingly, it is assumed that eosinophils and their (patho-) physiological functions are governed by a sensitive prostanoid signaling network. In this review, we specifically focus on the functions of PGD2, PGE2 and PGI2 and their receptors on eosinophils. We discuss their significance in allergic and non-allergic diseases and summarize potential targets for drug intervention.